Linke Waffe Kunst die Kommunistische Studentenfraktion am Bauhaus - Thöner, Wolfgang 1957-; Strob, Florian 1985-; Schätzke, Andreas 1964- (Bauwelt Fundamente, 2022)
Internal criticism of the Bauhaus For a long time, the topic of far-left currents within Bauhaus was one of controversy. Thanks to recent research on the Communist Student Fraction (Kostufra), the leftist students are finally coming into focus. Their magazine: bauhaus. sprachrohr der studierenden. organ der kostufra was a venue for unsparing critique of events, curricula, and teachers. The journal was published between 1930 and 1932 in Dessau and Berlin in 15 hectographed issues in a loose-leaf collection and is critically discussed here for the first time by researchers from art and cultural studies, architecture, and editorial studies. It clearly demonstrates that the experimental value of Bauhaus cannot be separated from its political radicalism.